Towards a Taxonomy of Bullshit Illocutionary Acts: A Reply to Gascón and Mukerji and Mannino - Picazo, Gustavo (Informal Logic)

(untitled) (Informal Logic, 2025)
I propose redefining Gascón’s (2021) notion of argumentative bullshit by adding three words to its original formulation. Consequently, argumentative bullshit would be defined as the production of an argument without concern for the strength of the supporting relation between the reasons and the claim. I then examine Mukerji and Mannino’s (2022) general account of argumentative bullshit. Using Grice’s conversational maxims, I show how it can be further extended into a taxonomy of bullshit illocutionary acts—an extension Gascón himself hints at.